An exploratory study on goal programming as an alternative method to develop prediction equations - Lau, Chik Kong (2004)
One of the most promising techniques for multiple objective decision analysis is goal programming. Goal programming is a powerful tool which draws upon the highly developed and tested technique of linear programming, but provides a simu~taneousolution to a complex system of competing objectives. Least squares method in regression analysis is also a popular technique used in decision making. It is an approach used in the study of relations between variables, particularly for the purpose of understanding how one variable depends on one or more other variables. However, one of the main problems is that the method of least squares is biased by extreme cases. This study proposes goal programming as an alternative to analyze such problems. The analysis were done by using QM for Windows and MINITAB software package.